WOMEN IN CONTROL: A STUDY ON BODY AND GENDER FROM A BRAZILIAN GAMER COMMUNITY - Moura, Catherine; Messias, José (AoIR Selected Papers of Internet Research, 2026)
This article discusses female participation in the culture of digital games, an environment still dominated by men, a determining factor in the exclusion and harassment of female audiences. We seek to understand female mobilization to remain in the gamer community as a practice of sociability and a way of tensioning its misogynistic structures. In addition to assuming a neutral pseudonym, through nicknames, many women look for representative groups or communities to form teams or even to build their online friendship network. Given this scenario, we carried out a virtual ethnography in a closed community of female gamers on the social network Facebook. The objective was to understand their experiences in a space considered safe and welcoming.